Photosynthesis impairments precede noticeable changes in leaf water status of mango plants infected by Ceratocystis fimbriata - Bispo, Wilka M. S.; DaMatta, Fábio M.; Araujo, Leonardo; Cacique, Isaías S.; Rodrigues, Fabrício A (European Journal of Plant Pathology, 2016)
Mango wilt, caused by Ceratocystis fimbriata, is a disease of great economic importance in mango production. Considering that the physiological effects of this vascular disease are not fully characterized, this study aimed to investigate some alterations in mango leaves from cultivars Ubá and Tommy Atkins, respectively, resistant and moderately resistant to mango wilt. The relationships between relative lesion indices (upward relative lesion length (URLL), the downward relative lesion length (DRLL) and the radial fungal colonization (RFC)) and water relations and gas exchange and chlorophyll a fluorescence parameters were evaluated at 10, 20 and 30 days after inoculation. The foliar concentrations of lipid peroxidation, total pigments and total free amino acids and proline were also determined. The URLL, DRLL and RFC increased overtime in both Ubá and Tommy Atkins cultivars, but reached the greatest values for cv. Tommy Atkins. Although cultivars did not present contrasting results for most of the evaluated parameters, the relative changes between inoculated and non-inoculated plants of each cultivar were more disparate in plants from cv. Tommy Atkins. There were decreases of 55, 73, 65 and 22 %, respectively, for net carbon assimilation rate (A), stomatal conductance to water vapor (g s), transpiration rate (E) and internal-to-ambient CO2 concentration ratio (C i/C a) for inoculated plants from cv. Tommy Atkins in comparison to the non-inoculated plants. For inoculated plants from cv. Ubá, there were decreases of 25, 41 and 36 % for A, g s and E while C i/C a decreased by 17 % in relation to the non-inoculated plants. Inoculated plants of cvs. Tommy Atkins and Ubá showed pronounced reductions for midday leaf water potential and apparent hydraulic conductance relative to the control. Inoculated plants from cv. Ubá showed values of predawn leaf water potential that were 25 % higher in comparison to inoculated plants from cv. Tommy Atkins. In addition, decreases in total chlorophyll concentration as well as increases in free amino acids and lipid peroxidation occurred for inoculated plants from cv. Tommy Atkins.
Keywords: Gas exchange; Chlorophyll a fluorescence; Mango wilt; Osmotic adjustment, vascular pathogen; Water potential